Aplikativna razvojna tipologija hribovskih kmetijskih gospodarstev v občini Ribnica na Pohorju - Kerbler, Boštjan Kefo (Geografski vestnik, 2003)
With new approaches to the development of the rural areas, farming has become the most important for ensuring the development of areas with difficult natural production conditions - it sustains the economic stability, the stability of the population, as well as the social, the cultural and the ecological stability of the landscape. With the aim of defining developmental starting points of rural areas in the municipality Ribnica na Pohorju, the article presents the synthesis of the results obtained through the empirical research based on the quantitative analysis of data gained in the field research. The results are determined as indicators for creating the applied developmental typology of farms in a certain area in the research. On the basis of the situation and processes in the part of the farms classified as developmentally regressive, the conclusion gives the starting points for the sustainable development of rural areas in the municipality Ribnica na Pohorju.
Keywords: agrarna geografija; hribovska območja; agriculture; kmetijstvo; hribovsko kmetijstvo; sonaravni razvoj; razvojna strategija; Pohorje; Ribnica na Pohorju